Innovative Technology of Accelerated Composting of Chicken Manure to Obtain an Organic Fertilizer with a High Content of Humic Acids (Agricultural Engineering, 2022)
One of the most important fractions of soil organic matter which has significant environmental and agricultural importance is humus. The specific humus compounds of soil include the complex of amorphous organic humic substances which include humic acids, fulvic acids and humins. The effectiveness of the natural formation of active humic substances during composting processes depends on the chemical composition of organic residues and the environmental conditions influencing the development and activity of native microorganisms. The aim of the project was to build innovative composting boxes for chicken manure that allow to effectively obtain a fertilizer with the highest possible content of humic acids, by creating perfect and controlled conditions for the rapid development of indigenous thermophilic microorganisms and by combining it with the owned bio-acceleration technology. For perfect conditions (temperature, humidity, oxygen, pH) for the controlled growth of microorganisms, an algorithm of the dependence of the box operation parameters on the course of the biological process, was built. The product obtained after composting is an easily digestible complex organic fertilizer of brown-black colour, pH 7.5-8.0 and NPK 5:3:4 and a high content of native humic acids. Its use increases the growth of green mass of plants and improves soil fertility, which has been proved by the conducted pot research.